Na+ -activated K+ channels protect against overexcitation and seizure-like behavior in Drosophila - Byers, Nathan S., author; Tsunoda, Susan, advisor; Garrity, Deborah, committee member; Hentges, Shane, committee member; Hoerndli, Frederic, committee member; Tamkun, Michael, committee member (Colorado State University. Libraries, 2021)
Na+-activated K+ channels (KNa) encode K+ channels that are activated by internal Na+ and are widely expressed throughout the mammalian central nervous system. Based on the biophysical properties of the channels, it has long been postulated that they act as a reserve mechanism to combat neuronal overexcitation. Specifically, early electrophysiological recordings suggested that only when intracellular Na+ levels rise significantly, for instance in neuropathological conditions, do KNa channels become active. More recent evidence suggests that they may function under normal physiological circumstances by means of binding cytoplasmic factors and via the persistent Na+ current. However, to date it is unclear if KNa channels function to prevent overexcitation in vivo. Therefore, research in my dissertation sets out to test the hypothesis that KNa channels protect against overexcitation in Drosophila models of epilepsy. Drosophila contain one gene encoding a KNa channel, dSlo2. In the third chapter of this dissertation, I examine expression of dSlo2 channels throughout the nervous system. Findings from this chapter show that dSlo2 channels are expressed in cholinergic neurons, the main excitatory neuron of the Drosophila brain. Furthermore, dSlo2 channels were excluded from GABAergic neurons. I additionally found that dSlo2 channels are localized to axonal regions of multiple neuronal subtypes in the nervous system. Thus, these results suggest that as K+ channels widely and preferentially expressed in excitatory neurons in the brain, dSlo2 channels may function to dampen neuronal, and perhaps behavioral, excitability. In Chapter 4, I test the hypothesis that dSlo2 channels protect against behavioral abnormalities caused by cholinergic overexcitation. I first show that the loss of dSlo2 exacerbates behavioral deficits and death associated with prolonged exposure to a cholinergic agonist, Imidacloprid. Furthermore, I found that adult flies lacking dSlo2 exhibit mechanically induced seizure-like behavior following feeding of Imidacloprid, which does not occur in wild-type flies. Combined, these results suggest that dSlo2 channels do indeed protect against cholinergic overexcitation. It has previously been shown that mammalian KNa channels are activated by a persistent Na+ current (INaP) in neurons, suggesting that these channels may ameliorate behavioral consequences of an increased INaP in vivo. In Chapter 5, I test the hypothesis that dSlo2 channels protect against Drosophila seizure-like behavior induced by an increased INaP. I find that the loss of dSlo2 significantly exacerbates seizure-like behavior in multiple Drosophila epileptic models, including a model for human generalized epilepsy with febrile seizures plus (GEFS+). Additionally, the absence of dSlo2 worsens seizure-like behavior when flies are exposed to Veratridine, a pharmacological agent known to increase INaP. Interestingly, the loss of dSlo2 also revealed a spontaneous seizure phenotype in INaP-affected seizure models that was otherwise absent. Altogether, these results are consistent with the model that KNa channels are activated by INaP, and protect against seizure-like behavior actuated by increased INaP. Overall, the work in my dissertation expands our understanding of the role of KNa channels. These findings suggest that KNa channels may play a protective role for many neuropathological diseases associated with an increased INaP, such as epilepsy, amyotrophic lateral sclerosis, neuropathic pain, and ischemia.
Keywords: ion channels; sodium-activated potassium channels; persistent sodium current; epilepsy